PERBANDINGAN HASIL BELAJAR EKONOMI MENGGUNAKAN MODEL PEMBELAJARAN INQUIRY TERBIMBING DAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TEAMS ASSISTED INDIVIDUALIZATION KELAS X SMA NEGERI I SEKINCAU - Euis Dwi Eka Kurnia; Yesi Budiarti (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
The teacher learning process plays a role to determine an effective learning method and supports students to gain valuable experience. The method has a significant contribution in teaching and learning activities. Achieving the right learning goals can be achieved with the right method. The purpose of this study is 1) to find out whether there are differences in the average economic learning outcomes using a guided inquiry learning model and TAI type Cooperative Learning Model at the X grade of SMA Negeri 1 Sekincau 2017. 2) What is the average economic learning outcomes using the guided inquiry learning model is higher than the TAI type Cooperative Learning Model for X grade students of SMA Negeri 1 Sekincau 2017. This research is ex post facto experimental research which is the influence of guided inquiry learning model and TAI type Cooperative Learning Model at the X grade of SMA Negeri 1 Sekincau Year 2017. The population in this study is X grade students of SMA Negeri 1 Sekincau with totaling 32 students and those who were sampled in this study of X14 grade with totaling 30 students. Based on the results of the research data analysis at the level of 5% is 1.67 shows that thit > tdaf thus the conclusions obtained that H0 was and H1 was accepted, which means that the learning uses a guided inquiry model is greater than learning using the TAI type cooperative learning model. Based on the research conducted, it is known that the use of the guided inquiry model (69.40) further improves student learning outcomes when compared with the use of the TAI type cooperative learning model (61.15). Keywords: Comparison of real economic learning, Guided Inquiry Learning Model and Cooperative Learning Type Teams Assisted Individualization (TAI).